Cho \(z = a + bi\). Chứng minh rằng :
a) \({{z^2} + {{\left( {\bar z} \right)}^2} = 2\left( {{a^2} - {b^2}} \right)}\)
b) \({{z^2} - {{\left( {\bar z} \right)}^2} = 4abi}\)
c) \({{z^2}.{{\left( {\bar z} \right)}^2} = {{\left( {{a^2} + {b^2}} \right)}^2}}\)
a)
\(\begin{array}{l}
{z^2} + {\left( {\bar z} \right)^2} = {(a + bi)^2} + {(a - bi)^2}\\
= {a^2} - {b^2} + 2abi + ({a^2} - {b^2} - 2abi) = 2\left( {{a^2} - {b^2}} \right)
\end{array}\)
b)
\(\begin{array}{l}
{z^2} - {\left( {\bar z} \right)^2} = {(a + bi)^2} - {(a - bi)^2}\\
= {a^2} - {b^2} + 2abi - ({a^2} - {b^2} - 2abi) = 4abi
\end{array}\)
c) \({z^2}.{\left( {\bar z} \right)^2} = {(a + bi)^2}.{(a - bi)^2} = {[(a + bi)(a - bi)]^2} = {\left( {{a^2} + {b^2}} \right)^2}\)
-- Mod Toán 12
Copyright © 2021 HOCTAP247